Human telomeric position effect is determined by chromosomal context and telomeric chromatin integrity - Koering, Catherine Elaine; Pollice, Alessandra; Zibella, Maria Pia; Bauwens, Serge; Puisieux, Alain; Brunori, Michele; Brun, Christine; Martins, Luis; Sabatier, Laure; Pulitzer, John F.; Gilson, Eric (EMBO reports, 2002)
We investigated the influence of telomere proximity and composition on the expression of an EGFP reporter gene in human cells. In transient transfection assays, telomeric DNA does not repress EGFP but rather slightly increases its expression. In contrast, in stable cell lines, the same reporter construct is repressed when inserted at a subtelomeric location. The telomeric repression is transiently alleviated by increasing the dosage of the TTAGGG repeat factor 1 (TRF1). Upon a prolongated treatment with trichostatin A, the derepression of the subtelomeric reporter gene correlates with the delocalization of HP1α and HP1β. In contrast, treating the cells with 5 azacytidin, a demethylating agent, or with sirtinol, an inhibitor of the Sir2 family of deacetylase, has no apparent effect on telomeric repression. Overall, position effects at human chromosome ends are dependent on a specific higher‐order organization of the telomeric chromatin. The possible involvement of HP1 isoforms is discussed.